Disability status and student outcomes over time in regular classrooms: Evidence from a national panel survey in China. (October 2019) - Ge, Zhongming; Zhang, Yueyun
Abstract: The idea of inclusive education suggests that student with disabilities should be educated in regular schools, instead of being placed in segregated special education sectors. However, little is known about whether students with and without disabilities could follow parallel paths of development within the same classroom, especially in developing countries. Drawing upon two waves of data from a nationally representative sample of Chinese middle school students (sample size, 8252; mean age, 12.6 years; disability prevalence, 8%), we employed multiple regressions with class fixed effects and the change score method to examine the association between disability status of students and temporal changes in various developmental domains, including cognitive ability, school attachment, and emotional wellbeing). Our results showed that students with disabilities were disadvantaged on wave-specific outcomes, but not on between-wave changes. There was indeed some heterogeneity across various aspects of development. Specifically, the observed gains in cognitive ability and school attachment during the follow-up period were not significantly affected by disability status, net of individual and family background and class fixed effects. In addition, although both students with and without disabilities experienced a temporal decline in emotional wellbeing, the decline was larger among students without disabilities, pointing to a convergence of mental health between students with and without disabilities within the same regular classrooms. These findings contribute to the understanding of the relationship between inclusive education and development of both students with and without disabilities in less developed educational context.